Conservation and utilization of sweet potato genetic diversity in Asia: Proceedings of second Asian Network for Sweet Potato Genetic Resources. 3-5November 1999, Bogor, Indonesia - Ramanatha Rao, V.; Hermann, M. (2001)
These proceedings have been compiled and edited based on the papers presentedat this workshop, dealing with objectives as set by ANSWER members. They contain the information on the progress made during the three years since the members met last time, but more importantly they record the commitments made by different partners for furthering sweetpotato genetic resources work in Asia. They also contain the recommendations on strategies and approaches proposed at the workshop, which will form the basis for future work of ANSWER. It is my hope that the publication and distribution of this volume will stimulate further the already vigorous activity in sweetpotato genetic resources conservation and use in the region.